Analysis of the Impact of Mining Activities on Flooding in Pangkalpinang City - Salim, M. Agus; Suroso, Agus (ASTONJADRO, 2025)
Flooding is one of the problems in Pangkal Pinang City. Tin mining activities in the districts around Pangkal Pinang City have triggered flooding in Pangkal Pinang City Apart from that, the reduction in catchment areas and sub-optimal polder system infrastructure affect the height and duration of flood inundation in Pangkal Pinang City. Flood management is currently still partial, so it is necessary to carry out integrated coordination between agencies and institutions to review the master plan for flood management in Pangkal Pinang City. To prevent flooding, it is necessary to review the things that cause flooding, so research needs to be carried out to analyze these things. This research aims to determine and analyze the influence of mining activity factors, catchment areas, polder systems and coordination on flood conditions in Pangkal Pinang City. This research uses a multiple linear regression analysis model with supporting data from historical data on the height and average duration of flood inundation in Pangkal Pinang City. The research results showed that the model equation Y = 3.216 + 0.484X1 – 0.396X2 – 0.412X3 – 0.480X4. Based on the results of data analysis using SPSS, the results showed that mining activity factors, catchment areas, polder systems and coordination had an influence on flood conditions in Pangkal Pinang City with an influence contribution of 85.0% with the most dominant variable ranking influencing flooding, namely mining activity. The regression coefficient value for the mining activity variable has a positive value of 0.484. This shows that if mining activity increases by 1%, then the height and duration of flooding as a flood indicator will increase by 0.484 times assuming other independent variables are considered constant. This model is used to project future floods. With this modeling, it is hoped that it can be used to overcome flooding in Pangkal Pinang City.